Seawater desalination technology - CHIN-AN CHENG (2014)
The invention discloses a seawater desalination technology. The seawater desalination technology is characterized in that a seawater desalination device is installed in a position having depth more than 270m in deep sea, seawater enters into a multistage precipitate filter under the action of hydrostatic pressure of seawater, the filtered clean seawater goes through a pipe and then enters into a crossflow-type RO filter under the action of hydrostatic pressure-atmospheric pressure difference as reverse osmosis powder, the separated fresh water goes through a pipe and then is stored in a fresh water storage tank in the position having the same depth, the fresh water in the fresh water storage tank is sucked and fed to a water distribution system on the sea surface by a fresh water delivery pump driven by external wave and is used for water distribution, and the separated concentrated salt water is output and re-discharged to sea by a salt water delivery pump driven by external wave. The seawater desalination t